2021
DOI: 10.21203/rs.3.rs-452779/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increasing Medicinal and Phytochemical Compounds of Coneflower (Echinacea Purpurea L.) Medicinal Plant using New Hydroponic Culture Media and Nutrition Pattern

Abstract: Medicinal plants are considered as one of the most important sources of chemical compounds, so preparing a suitable culture media for medicinal plant growth is a critical factor. The present study is aimed to improve the caffeic acid derivatives and alkylamides percentages of Echinacea purpurea root extract by optimizing the NO3-/NH4 + ratio in new hydroponic culture media. Perlite particle size in the growing media was varied as very coarse perlite (more than 2 mm), coarse perlite (1.5-2 mm), medium perlite (… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…This suggests that growing conditions and environmental factors strongly affect the composition of essential oil. 27 The study conducted by Simun Kolega et al showed that growing basil plants in fortified nutrient solutions resulted in an increase in the accumulation of biomass and nutraceutical compounds. Modulation of more than 400 secondary metabolites was observed, including phenylpropanoids, isoprenoids, alkaloids, several flavonoids, and terpenoid molecules.…”
Section: Applications Of Hydroponics For Growing Medicinal Plantsmentioning
confidence: 99%
“…This suggests that growing conditions and environmental factors strongly affect the composition of essential oil. 27 The study conducted by Simun Kolega et al showed that growing basil plants in fortified nutrient solutions resulted in an increase in the accumulation of biomass and nutraceutical compounds. Modulation of more than 400 secondary metabolites was observed, including phenylpropanoids, isoprenoids, alkaloids, several flavonoids, and terpenoid molecules.…”
Section: Applications Of Hydroponics For Growing Medicinal Plantsmentioning
confidence: 99%